2020
DOI: 10.3390/cancers12071954
|View full text |Cite
|
Sign up to set email alerts
|

Use of Interferon Alfa in the Treatment of Myeloproliferative Neoplasms: Perspectives and Review of the Literature

Abstract: Interferon alfa was first used in the treatment of myeloproliferative neoplasms (MPNs) over 30 years ago. However, its initial use was hampered by its side effect profile and lack of official regulatory approval for MPN treatment. Recently, there has been renewed interest in the use of interferon in MPNs, given its potential disease-modifying effects, with associated molecular and histopathological responses. The development of pegylated formulations and, more recently, ropeginterferon alfa-2b has resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 80 publications
1
39
0
Order By: Relevance
“…A major significance of Peg-IFNα-2a is its ability to target MPN stem cells and reduce mutant allele burden in MPN [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Sustained molecular, haematological response and regression of BM fibrosis were seen in some patients after discontinuation of Peg-IFNα-2a, indicating the eradication of MPN stem cells [ 65 , 69 ] ( Table 2 ).…”
Section: Current Therapeutic Options In Mpn and Their Effects On Mmentioning
confidence: 99%
“…A major significance of Peg-IFNα-2a is its ability to target MPN stem cells and reduce mutant allele burden in MPN [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Sustained molecular, haematological response and regression of BM fibrosis were seen in some patients after discontinuation of Peg-IFNα-2a, indicating the eradication of MPN stem cells [ 65 , 69 ] ( Table 2 ).…”
Section: Current Therapeutic Options In Mpn and Their Effects On Mmentioning
confidence: 99%
“…Another drawback of interferon use is the tedious dosing regimen (thrice weekly injections, approximately three million units per dose). Pegylated interferons were introduced to overcome this major disadvantage, and they also offer a better side effect profile [29]. Studies have shown that low-dose pegylated interferon alpha 2 has an even better efficacy when given in combination with ruxolitinib, characterized by improvement in cell counts and the bone marrow picture, reduced JAK2V617F mutation burden, and adequate amelioration of symptoms [30].…”
Section: Interferonsmentioning
confidence: 99%
“…Studies have shown that low-dose pegylated interferon alpha 2 has an even better efficacy when given in combination with ruxolitinib, characterized by improvement in cell counts and the bone marrow picture, reduced JAK2V617F mutation burden, and adequate amelioration of symptoms [30]. The most commonly reported adverse effects with its use include malaise, myalgias, nausea, vomiting, and depressive episodes [29]. In an attempt to counteract these undesirable effects and retain the efficacy of this drug, a newer formulation has been devised, known as ropeginterferon alfa-2b.…”
Section: Interferonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the current therapies, only allogenic stem cell transplantation is curative, capable of resolving bone marrow fibrosis and the malignant clone ( 28 ). Interferon-alpha is similarly promising, and while initially associated with treatment-limiting toxicities, the development of pegylated-interferon has made cytogenetic remission with this agent a real possibility ( 29 , 30 ). The JAK1/2 kinase inhibitor ruxolitinib was approved by the United States Food and Drug Administration in 2011 for high risk MF patients and in 2014 for certain PV patients ( 31 33 ).…”
Section: Mpn Driving Mutations Cell Signaling and Targeted Therapiementioning
confidence: 99%